2020
DOI: 10.2147/ceor.s229685
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Cost-Effectiveness of Universal Varicella Vaccination in Italy: A Model-Based Assessment of Vaccination Strategies</p>

Abstract: Background: In 2017, varicella vaccination became mandatory for all children in Italy, based on a two-dose schedule administered at 12-15 months of age and 5 to 6 years of age. Varicella vaccines are available in different formulations (as a single vaccine or as a combination vaccine together with measles, mumps, and rubella) and are made by multiple manufacturers with different effectiveness profiles. This study calculates the cost-effectiveness of a range of varicella vaccination strategies to identify the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 54 publications
(61 reference statements)
5
24
0
Order By: Relevance
“…These results are consistent with applications of the same dynamic transmission model to other countries [ 13 , 27 , 39 ]. Applied to Turkey, two-dose strategies of universal childhood varicella vaccination were projected to reduce varicella incidence by 99% after 25 years and to be cost-effective [ 13 ].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…These results are consistent with applications of the same dynamic transmission model to other countries [ 13 , 27 , 39 ]. Applied to Turkey, two-dose strategies of universal childhood varicella vaccination were projected to reduce varicella incidence by 99% after 25 years and to be cost-effective [ 13 ].…”
Section: Discussionsupporting
confidence: 87%
“…The least impactful strategy in terms of cost-effectiveness and resource utilization was strategy D (V-GSK at 15 months and MMRV-GSK at 11 years). These results are consistent with applications of the same dynamic transmission model to other countries [13,27,39]. Applied to Turkey, two-dose strategies of universal childhood varicella vaccination were projected to reduce varicella incidence by 99% after 25 years and to be cost-effective [13].…”
Section: Plos Onesupporting
confidence: 74%
See 2 more Smart Citations
“…A transmission cost-effectiveness model applied to simulate the costs and outcomes associated with varicella vaccination strategies showed that over the next 50 years, in the absence of universal varicella vaccination, there would be varicella cases, deaths, and related costs [16]. On the contrary, a vaccination program by the least expensive strategy may lead to a 66% decrease in varicella cases and 30% reduction in varicella-related deaths, with a great saving in societal cost.…”
Section: Discussionmentioning
confidence: 99%